On nonsmooth multiobjective semi-infinite programming with switching constraints using tangential subdifferentials - Jennane, Mohsine; Kalmoun, El Mostafa (Statistics, optimization & information computing, 2023)
We investigate optimality conditions for a nonsmooth multiobjective semi-infinite programming problem subject to switching constraints. In particular, we employ a surrogate problem and a suitable constraint qualification to state necessary M-stationary conditions in terms of tangential subdifferentials. An example is given at the end to illustrate our main result.